The Acquisition of Chinese as a First and Second Language - Wen, Xiaohong (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This volume, through highly selective and rigorous review processes, has collected eight empirical studies showcasing research advances in multiple domains including child first language, adult additional language, and heritage language acquisition. The studies are theoretically motivated and have adopted a spectrum of innovative methodological strategies to achieve a broader understanding of the nature of learning and the learning process. The volume encompasses a wide range of contents: 1) The L1 and L2 acquisition of syntax, semantics, phonetics, and the syntax-discourse interface; 2) Data comparisons across different learner groups: L1 Chinese children, L2 Chinese learners, and Chinese heritage speakers; 3) Acquisition of language skills: speaking, listening, and writing; and last but not least, 4) Instructional interventions including consciousness-raising and metacognitive strategy training. The volume is intended to bridge the gap between research and instruction by helping teachers understand their students and their learning. Informed by research, teachers can opt for appropriate pedagogical approaches and instructional conditions for their students. The volume is guest-edited by Xiaohong Wen, Professor in Applied Linguistics and Chinese language Acquisition at the University of Houston.